Enhancing EFL Young Learners’ Engagement in English Learning Through Digital Storytelling - Don Evan Hernando; Emeral Emeral; Sulamit Syeba; Fadila Umi Khodijah; Misericordias Domini (Jurnal Pemberdayaan Masyarakat dan Komunitas, 2026)
This community service project implemented the digital storytelling to enhance English language engagement among young learners at a community-based learning centre in Palangka Raya, Central Kalimantan, Indonesia. The project addressed challenges faced by elementary and junior high school students who have limited access to interactive, technology-based learning resources and lack authentic exposure to English outside the classroom. The project involved 19 participants aged 7-14 years old who engaged in storytelling sessions. The results showed a significant improvement in participant engagement, with 94.74% of participants reporting a high satisfaction with the storytelling method. Participants also expressed strong interest in the storytelling method and suggested adding more interactive elements such as games and songs. The findings confirms that digital storytelling can be an engaging and effective way of educational approach for teaching English.